Community Acceptance of Blue Energy: Identifying Future Research Trajectories for Understanding “Place-Technology-Fit” Perceptions - Axon, Stephen (Blue Economy: People and Regions in Transitions, 2022)
Offshore renewable, or Blue Energy, installations are a crucial component of many countries’ energy policies and pathways towards a sustainable low-carbon
Num Pages: 14
Keywords: dept.egm